Biofuel in Yemen; an alternative energy resource toward sustainability - Fozy Binhweel (Progress in Engineering Application and Technology, 2022)
Yemen, as one of the third world countries, heavily depends on fossil fuel as a primary resource of energy. Despite being an oil exporter, the country, with around 30 million population, lacks the accessible energy for a long time. Outbreak of the armed conflict in 2015 made matters worse. Hindering oil industry, falling oil imports to 1 %, and losing 90 % of the Yemeni people for the public power supplies are among the manifestations. Besides the energy scarcity, Yemen is in the list of the top three countries generating biomass wastes in the Middle East and North Africa Region (MENA). Around 3.8 million tons of wastes are generated annually, mostly agricultural residues and organic wastes. People used the discarded biomass to utilize their own energy needs in a primitive method like fuelwood and charcoal. The bright side is that these amounts of discarded biomass can open horizons to biofuel industry. Biofuel is a promising and sustainable energy resource to meet the energy demands in Yemen. The biofuel products, which include biodiesel, biogas, and bio-oil, are suitable substitute for the conventional petroleum fuel without any modifications in the engines, storing, and transporting gadgets. Even though, modest initiatives and projects were launched to exploit the discarded biomass for biofuel production in Yemen, this paper intends to overview the energy status in Yemen and review the studies regarding biofuel productions on both lab and industrial scales to meet the country’s energy demand, considering the economic and environmental impacts.